ANALISIS IN-SILICO PROTEIN DnaJ Bacilus stearothermophilus - Kumaunang, Maureen; Kamu, Vanda S.; Mandik, Yohanis I. (CHEMISTRY PROGRESS, 2009)
DnaJ is a chaperone which has function in facilitating folding, translocation, and degradation of protein.The aim of this research was to undertake in silico study of DnaJ protein from Bacillus stearothermophilus.Structure analysis of DnaJ B. stearothermophilus showed that it has J-domain which has two conservedmotifs, i.e. HPD and QKRA motifs. It also has cys-rich domain which has one conserved motif, i.e.CXXCXGXG. Structure prediction of DnaJ B. stearothermophilus showed that it has similar structure of Jdomainand cys-rich domain with that of DnaJ Escherichia coli.